2014
DOI: 10.1002/jaal.333
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Substance

Abstract: The authors describe an accessible and adaptable approach to teaching revision to high school writers. Students reflect, communicate, and take action to substantively revise writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In their comments, two participants stated that the online peer reviews helped them reflect on their strengths and weaknesses in their writing, which was also reported by Tsui and Ng (2000). Two other participants said they appreciated learning from their peers' writings, something also noted by Early and Saidy (2014). An interviewee supported this view and indicated that they became more aware of their own writing structures through comparing their writings with their classmates.…”
Section: Efficacymentioning
confidence: 81%
See 1 more Smart Citation
“…In their comments, two participants stated that the online peer reviews helped them reflect on their strengths and weaknesses in their writing, which was also reported by Tsui and Ng (2000). Two other participants said they appreciated learning from their peers' writings, something also noted by Early and Saidy (2014). An interviewee supported this view and indicated that they became more aware of their own writing structures through comparing their writings with their classmates.…”
Section: Efficacymentioning
confidence: 81%
“…S tudent peer review is considered an essential part of the process approach to EFL/ESL writing for several reasons. For example, peer reviews enable learners to reflect on the strengths and weaknesses of their writing, promote their awareness of the audience (Tsui & Ng, 2000), and facilitate improved revisions (Early & Saidy, 2014). To make peer reviews successful, collaboration among learners plays an important role because it helps learners to negotiate meaning and reflect on their writing (Lockhart & Ng, 1995).…”
mentioning
confidence: 99%